Unveiling Political Bias in English Newspapers of Indonesian News Portal: A Critical Discourse Analysis Approach - Faza Afifah Ghina Putri Abdilah; Izzati Gemi Seinsiani (Universitas Islam Negeri Palopo, 2026)
English language news portals have become important cites where political narratives are built for both local and global viewers as press freedom wanes in Indonesia and media ownership grows more concentrated. Although Indonesian media has seen increasing academic attention, few studies using Critical Discourse Analysis (CDA) have looked at how pro-government bias works linguistically in English-language political coverage during electoral cycles. Using Fairclough's three-dimensional CDA model on 25 news articles from four Indonesian online news portals such as, The Jakarta Post, Tempo English, Republika, and Antara News published during the 2024 presidential election, this study addresses that gap. A 16-point instrument assessing source selection, lexical choices, framing techniques, and information balance was used to judge articles. Results show that 56% of articles showed pro-government bias, with an average score of 4.52/16. During pre-election and election month times, bias levels were much greater than those in the post-election period. Pro-government bias was purposely created by means of partisan evaluative language, calculated source quoted, and strategic headline framing. The manifestation and intensity of bias were determined by contextual variables like temporal proximity to the election, issue sensitivity, law enforcement climate, and media channel attributes. The research shows how English language Indonesian political news systematically creates ideological positioning using language and frame strategies, therefore helping to explain bias mechanisms more generally in non-Western, EFL media environments.